PEMAHAMAN KONSEPTUAL MATEMATIS SISWA SMA PADA ERA COVID-19 - M Sani; Halini Halini; Romal Ijuddin (Jurnal AlphaEuclidEdu, 2023)
This study aims to describe how high school students learned trigonometric comparison material in right triangles online and at home during the Covid-19 pandemic in the context of their level of conceptual mathematical understanding. Survey methods are combined with descriptive research methods in this type of study. This information comes from the results of tests and interviews with 32 Grade XI SMA Negeri 7 Pontianak students about a wide range of topics. The designed tool is a test that is related to the problem of understanding mathematical concepts for the purposes of this study. It is given to the research subjects and six students are chosen for the interview process. The findings of the research revealed that even in the midst of this epidemic, the level of conceptual understanding of mathematics students learning online remains low.